The emergence of modern sea ice cover in the Arctic Ocean - Knies, Jochen; Cabedo-Sanz, Patricia; Belt, Simon T.; Baranwal, Soma; Fietz, Susanne; Rosell-Melé, Antoni (Nature Communications, 2014)
Source at https://doi.org/10.1038/ncomms6608 . Arctic sea ice coverage is shrinking in response to global climate change and summer ice-free conditions in the Arctic Ocean are predicted by the end of the century. The validity of this prediction could potentially be tested through the reconstruction of the climate of the Pliocene epoch (5.33–2.58 million years ago), an analogue of a future warmer Earth. Here we show that, in the Eurasian sector of the Arctic Ocean, ice-free conditions prevailed in the early Pliocene until sea ice expanded from the central Arctic Ocean for the first time ca. 4 million years ago. Amplified by a rise in topography in several regions of the Arctic and enhanced freshening of the Arctic Ocean, sea ice expanded progressively in response to positive ice-albedo feedback mechanisms. Sea ice reached its modern winter maximum extension for the first time during the culmination of the Northern Hemisphere glaciation, ca. 2.6 million years ago.